Enzymatic reaction kinetic and adsorption process in cyclodextrins production from selected starches - Shahrazi, Syahinaz (2015)
Two main processes in Cyclodextrins (CDs) production were studied in order to improve the industrial production. These processes are the enzymatic reaction of Cyclodextrin Glycosyl Transferase (CGTase) on starch which produces a mixture of CDs and other by-products, and the adsorption process on the enzymatic product mixture to obtain single CD. The CGTase enzymatic reactions on various starches were investigated by batch mode and dynamic mathematical modelling was proposed. Tapioca starch shows the highest CDs production of 23 g L-1 followed by sago (22 g L-1) and corn (19 g L-1) starch using 5% (w/v) initial starch concentration. From the experimental data of tapioca starch, Michaelis-Menten parameter which is also known as substrate limitation parameter, KM (58.23, 54.07 and 7.52 g L-1 for α-, β- and ɣ-CD, respectively) and maximum velocity of enzymatic kinetic, Vmax (3.45, 2.76 and 0.45 g L-1 min-1 for α-, β- and ɣ-CD, respectively) were obtained by linearization. Results show that the production of CDs was also affected by product inhibition, K1,i at the range of 9 to 0.8 g L-1 and degradation of CD rate by coupling reaction, CD,i at the range of 0.0046 to 0.658 min-1. Thus, all parameters were considered using the dynamic simulation and found that the exponential reaction kinetic model fitted the experimental data better. Results were supported by sensitivity analysis on K1,i parameter with impact of 8 – 18% difference from original data and validation experiment by using fed batch mode. In adsorption process, experimental results show the highest adsorption of α- CDs (700 mg g-1) was at low temperature (20˚C) and as temperature increase up to 50˚C, the adsorption of α-CDs reduce until 400 mg g-1. Fractogel EMDPhenyl retained α-CD as temperature increase from 20 until 50˚C, thus can be separated from β- and ɣ-CD. Adsorption of CDs onto Fractogel EMD-Phenyl adsorbent was preferred when compared to activated carbon (AC). The kinetic and isotherm adsorption studies were done by fitting the adsorption data with several models. The kinetic adsorption of CDs onto Fractogel EMD-Phenyl could be described by the pseudo-second-order kinetics model with R2 value of > 0.94 and SSE value < 28. The adsorption equilibrium data obeys the Temkin isotherm model with R2 value of > 0.84 and SSE value was less than 30.23. The adsorption activation energies obtained were at the range of 3 - 40 kJ mol-1.